2001
DOI: 10.1159/000052598
|View full text |Cite
|
Sign up to set email alerts
|

Volume Regulation of Thick Ascending Limb of Henle Cells: Significance of Organic Osmolytes

Abstract: The thick ascending loop of Henle (TALH) is exposed to high osmotic stress, which is particularly due to high sodium and chloride reabsorption and very low water permeability of the luminal membrane. Therefore, the volume regulation of TALH cells, derived from the TALH loop of rabbit kidneys, was analyzed. The volume was determined by impedance measurements. TALH cells, which were adapted to different osmolarities (300 and 600 mosm/l), showed no significant differences in their cell volume. Therefore, a comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
6
1
Order By: Relevance
“…The increment of NKCC2 protein in TALH cells results in long-term potentiation of NaCl reabsorbtion (Kim et al 1999;Besseghir et al 1986;Riazi et al 2009). Nevertheless, contradictory results exist on its participation in cell-volume regulation of TALH (Grunewald et al 2001;Eveloff and Calamia 1986). In the present study, we have found that, in contrast to NKCC1, hypertonic stress causes a significant downregulation in NKCC2 protein level with no obvious membrane translocation.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The increment of NKCC2 protein in TALH cells results in long-term potentiation of NaCl reabsorbtion (Kim et al 1999;Besseghir et al 1986;Riazi et al 2009). Nevertheless, contradictory results exist on its participation in cell-volume regulation of TALH (Grunewald et al 2001;Eveloff and Calamia 1986). In the present study, we have found that, in contrast to NKCC1, hypertonic stress causes a significant downregulation in NKCC2 protein level with no obvious membrane translocation.…”
Section: Discussioncontrasting
confidence: 54%
“…As regards to NKCC2, its three splice variants, identified along the thick ascending limb of loop of Henle (TALH) in the mammalian kidney, are partially inhibited by hypotonicity but to different extents (Plata et al 2002). NKCC2 seems not to respond to hypotonic stress in the eel intestine (Lionetto et al 2005) nor to hypertonic stress in rabbit TALH cells (Grunewald et al 2001). Few studies have directly addressed the regulation of NKCC expression in response to osmotic shock.…”
Section: Discussionmentioning
confidence: 99%
“…As an important part in the urinary concentration mechanism, renal tubular cells are able to restore their cell volume to normal despite high changes in extracellular osmolarity [27]. However; their adaptive mechanism has remained poorly characterized, and the underlying signaling pathways are poorly explored.…”
Section: Discussionmentioning
confidence: 99%
“…However, a previous study concluded (8) that 20-HETE inhibits Na ϩ -K ϩ -2Cl Ϫ cotransporter directly, because it decreased rather than increased the Na ϩ content of rabbit mTALH cells. However, only the steady-state Na ϩ content of the cells was measured by flame photometry after extensive washing of the cells with Na ϩ -free medium, and interpretation of this type of measurement can be difficult, since mTALH volume is regulated by opening of nonselective cation channels and cells lose intracellular Na ϩ and K ϩ when exposed to osmotic gradients (15). More recently, Na ϩ -sensitive fluorescent probes have been developed that allow for the dynamic measurement of changes in [Na ϩ ] i in proximal tubules (30,39) and mTALH (19).…”
mentioning
confidence: 99%